Deep Molecular Response Achieved with Chemotherapy, Dasatinib and Interferon α in Patients with Lymphoid Blast Crisis of Chronic Myeloid Leukaemia - Vráblová, Lucia; Divoký, Vladimír; Kořalková, Pavla; Poláková, Kateřina Machová; Kriegová, Eva; Janská, Romana; Grohmann, Jan; Holzerová, Milena; Papajík, Tomáš; Faber, Edgar (International journal of molecular sciences, 2023)
The treatment outcome in patients with chronic myeloid leukaemia (CML) in blast crisis (BC) is unsatisfactory despite the use of allogeneic stem cell transplantation (ASCT). Moreover, in some patients ASCT is contraindicated, with limited treatment options. We report the case series of two patients with lymphoid BC CML in whom ASCT was not approachable. The first patient developed BC two months after diagnosis in association with dic(7;9)(p11.2;p11.2) and T315I mutation. Blast crisis with central nervous system leukemic involvement and K611N mutation of the SETD2 gene developed abruptly in the second patient five years after ceasing treatment with nilotinib in major molecular response (MMR) at the patient's request. Both underwent one course of chemotherapy in combination with rituximab and imatinib, followed by dasatinib and interferon α (INFα) treatment in the first and dasatinib alone in the second case. Deep molecular response (DMR; MR 4.0) was achieved within a short time in both cases. It is probable that DMR was caused by a specific immune response to CML cells, described in both agents. The challenging medical condition that prompted these case series, and the subsequent results, suggest a re-visit to the use of a combination of well-known drugs as an area for further investigation.
Keywords: Dasatinib; dasatinib; interferon alfa; tyrosine kinase inhibitor; Protein Kinase Inhibitors; blastická krize; Humans; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; interferon alpha; Interferon-alpha; inhibitory proteinkinas; lidé; chronická myeloidní leukemie; Blast Crisis; chronic myeloid leukaemia; blast crisis